Penerapan Metode Permainan Edukatif untuk Meningkatkan Minat Belajar Siswa pada Mata Pelajaran PAI di Kelas X-I SMA Ar Rahman - Muthmainnah, Kamilia; Ginting, Nurman (Journal of Sustainable Education, 2025)
This study focuses on optimizing student enthusiasm in learning Islamic Religious Education (PAI) through the application of game-based learning strategies using digital technology such as Gimkit, Wordwall, Educaplay, and Bambiez. This research uses the Classroom Action Research (CAR) approach with the Kemmis & McTaggart model, conducted in two cycles, with 20 students from class X-1 of Ar Rahman High School as research subjects in the odd semester of the 2025/2026 academic year. Data was collected through learning interest observation sheets and field notes, then analyzed quantitatively using learning interest score percentages and qualitatively through descriptive analysis of changes in student behavior. The results showed an increase in the average learning interest from 72% in cycle I to 86% in cycle II, with the highest increase in the questioning activity indicator, from 65% to 82%. Thus, the application of digital educational games proved to be effective in creating a pleasant Islamic Education learning atmosphere, increasing motivation, and strengthening students' learning interest.